2014
DOI: 10.13073/fpj-d-13-00082
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Sandwich-Type Particleboard Panels Made from Rubberwood and Eastern Redcedar

Abstract: The objective of this study was to determine some of the mechanical properties of sandwich-type particleboard manufactured from rubberwood (Hevea brasilenesis) and Eastern redcedar (Juniperus virginiana). A total of 36 panels with two density levels of 0.65 and 0.75 g/cm3 were made using 10 percent urea-formaldehyde, a combination of 3 percent urea-formaldehyde and 10 percent cassava starch, and 10 percent cassava starch, respectively, as a binder. Three-layer panels with rubberwood fibers on the face layers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…There were no significant interaction effects on either the nail pull or face screw withdrawal strength. Panel density had the most important effect on the nail and face screw withdrawal strength, which agreed with previous studies (Cai et al 2004;Vassiliou and Barboutis 2005;Wang et al 2007). Figures 3 and 4 show positive trends of the nail and face screw withdrawal strength as density increased.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…There were no significant interaction effects on either the nail pull or face screw withdrawal strength. Panel density had the most important effect on the nail and face screw withdrawal strength, which agreed with previous studies (Cai et al 2004;Vassiliou and Barboutis 2005;Wang et al 2007). Figures 3 and 4 show positive trends of the nail and face screw withdrawal strength as density increased.…”
Section: Resultssupporting
confidence: 92%
“…Density plays an important role in the screw holding strength (Alma et al 2005). A previous study showed that there was a near-linear increase in face screw withdrawal strength as the density of the particleboard increased (Cai et al 2004;Vassiliou and Barboutis 2005;Wang et al 2007). In addition, the vertical and horizontal density profile influenced the screw withdrawal strength (Guler et al 2006;Wang et al 2007).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Some authors studied the production of biodegradable foam trays based on cassava starch blended with chitosan and Kraft fiber [ 20 ] or with sunflower protein and cellulose fiber [ 21 ]. Cassava starch, in combination with a small percentage of urea-formaldehyde resin, has been used as a binder in wood-based particleboards with densities of 650 and 750 kg/m 3 [ 22 ].…”
Section: Introductionmentioning
confidence: 99%